Can intangible capital explain cyclical movements in the labor wedge? - François Gourio; Leena Rudanko (Federal Reserve Bank of Chicago, 2014)
Intangible capital is an important factor of production in modern economies that is generally neglected in business cycle analyses. We demonstrate that intangible capital can have a substantial impact on business cycle dynamics, especially if the intangible is complementary with production capacity. We focus on customer capital: the capital embodied in the relationships a firm has with its customers. Introducing customer capital into a standard real business cycle model generates a volatile and countercyclical labor wedge, due to a mismeasured marginal product of labor. We also provide new evidence on cyclical variation in selling effort to discipline the exercise.
Keywords: E13; E32; 330; Business cycle; capital; labor wedge; Real Business Cycle; Immaterielle Werte; Beziehungsmarketing; Arbeitsproduktivität; Reallohn; Konjunktur; Theorie; USA